(3GdLhGeYs - (3eMeO Hf CMeO Hf eMeO Hf QTO GdbQWHj GdCfOdSj, CHh GdhdjO (B((3GdMajO(B)(3,J (B595 (3g` s
(3ChdgG (B:s
(3bGd Gdabjg GdbGVi CHhGdhdjO Hf QTO QVi Gddg Yfg GdZQV ai gPG Gdbhd s
(3BNQgG (B:s
(3hgfG GfbVi Gdbhd ai GdChbGjd GdcdjI ef Yde GdfaS s
(3hGdCbGhjd GdcdjI ef CbGhjd GdeaSQjf ai Yde GdfaSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B318 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B313s
(3eUOQ GbJfGA GdCUd (B:s
(3CSHGfjG (B- (3eOQjO (B(5000) s
Keywords: (3GdadSaI hGdefWbs